This woven kingdom - Mafi, Tahereh (Mafi, Tahereh. This woven kingdom (Series), 2022)
"To all the world, Alizeh is a disposable servant, not the long-lost heir to an ancient Jinn kingdom forced to hide in plain sight. The crown prince, Kamran, has heard the prophecies foretelling the death of his king. But he could never have imagined that the servant girl with the strange eyes, the girl he can't put out of his mind, would one day soon uproot his kingdom--and the world"--